2021
DOI: 10.1186/s12957-021-02226-1
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-490-3p inhibits migration and chemoresistance of colorectal cancer cells via targeting TNKS2

Abstract: Objective Colorectal cancer is one of the most common malignancy in the world. The oncogenesis of colorectal cancer is still not fully elucidated. It was reported that microRNA-490-3p (miR-490-3p) was closely related to the regulation of cancers. However, if miR-490-3p could also affect colorectal cancer and the specific mechanism remains unclear. Methods qRT-PCR was conducted to examine the expression of miR-490-3p. DIANA, miRDB, and TargetScan da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Additionally, miR-490-3p directly controlled RAB14 in CRC cells [48]. Expression of miR-490-3p affected cell viability and resistance to chemotherapy in CRC cells through regulating TNKS2 [35]. Our data also showed that ectopic expression of miR-490-3p significantly blocked malignant phenotypes of CRC cells, which is completely consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, miR-490-3p directly controlled RAB14 in CRC cells [48]. Expression of miR-490-3p affected cell viability and resistance to chemotherapy in CRC cells through regulating TNKS2 [35]. Our data also showed that ectopic expression of miR-490-3p significantly blocked malignant phenotypes of CRC cells, which is completely consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that tumor-suppressive function of miR-490-3p in CRC cells through targeting several oncogenic genes [35,36,47,48]. For example, ectopic expression of miR-490-3p blocked migration and invasion abilities in CRC cells [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, tankyrase 1 and 2 (TNKS1/2) are regulators of Wnt signaling by controlling the activity of the β-catenin destruction complex by reducing G1 cell cycle arrest and senescence ( Foronda et al, 2019 ). Mechanistically, TNKS2 is targeted by miR-490-3p, and its increased expression promoted the chemoresistance of colorectal cancer cells ( Li J. et al, 2021 ).…”
Section: Micrornas Involved In Ddp-chemoresistancementioning
confidence: 99%
“…The study conducted by Sasaki et al [106] just recently highlighted the importance of plasma miR-33a-5p to act as an effective biomarker for foresight on metastatic CRC chemotherapeutic success, focusing specifically on the typical first-line treatment combination of chemotherapeutic drugs, namely fluoropyrimidine + oxaliplatin + bevacizumab. The results of this study reveal that non-responders to CRC chemotherapeutic cycles had upregulated miR-33a-5p, indicating that patients with downregulated plasma levels for this miRNA would be more likely to respond to CRC chemotherapy [106] .…”
Section: Mirna Biomarkers For Crc Chemoresistancementioning
confidence: 99%